Antimicrobial Potential of Coleus Atropurpureus and its Metabolites Content: A Literature Review - Ayu Suci Pratiwi; Debby Handayati Harahap; Erizka Rivani (Jurnal Pengabdian Ilmu Kesehatan, 2025)
The increasing prevalence of multidrug-resistant bacterial infections underscores the urgent need for new antimicrobial agents, especially those derived from plant-based sources. Coleus atropurpureus, a medicinal plant used extensively in Asia and Oceania, contains various bioactive compounds, including flavonoids, terpenoids, and phenolic acids, which have demonstrated antimicrobial properties. This review examines studies published between 2015 and 2025, highlighting the antibacterial activity of ethanolic and methanolic extracts of C. atropurpureus, particularly against methicillin-resistant Staphylococcus aureus (MRSA). Phytochemical analysis reveals that these extracts exert their antimicrobial effects through multiple mechanisms, including the disruption of microbial membranes, enzyme inhibition, the induction of reactive oxygen species, and immunomodulatory actions. Furthermore, the extracts have shown synergistic effects when combined with antibiotics, suggesting their potential as adjunct therapies. The evidence gathered supports the therapeutic potential of C. atropurpureus as a natural antimicrobial agent, offering a promising alternative to conventional antibiotics in combating drug-resistant infections.